Synthesis and Antibacterial Activity of 2-Amino-4-(2’4’-Dichloro-5’-Fluorophen-1’-yl)-6-Aryl Pyrimidine Derivatives and Related Compounds - Bharucha, P.B.; Naik, H.B. (Asian Journal of Chemistry, 2010)
2´,4´-Dichloro-5´-fluorochalcone (1a-j) react with an alcoholic solution of guanidine nitrate containing aqueous sodium hydroxide solution to give the corresponding 2-amino-4-(2´,4´-dichloro-5´-flurophen-1´-yl)-6-aryl pyramidines (2a-j). Compounds (2a-j)were converted to diacetyl (3a-j); sulphonamide (4a-j); and N-acetyl sulphonamide (5a-j) pyrimidine derivitives. These varied products have been characterised by spectral studies and screened for antibacterial activity.